Obesity free - Papadopoulou, P.; Paggeiou, T.; Ntakoula, P.; Argyri, P. (Open Schools Journal for Open Science, 2020)
Regarding the theme of the United Nations Sustainable Development Goals, we decided to concern ourselves with the 3rd goal, “Good Health and Well-Being”, the 12th goal, “Responsible Consumption and Production” and the 17th goal, “Partnerships to achieve the Goal”. Concerning our action involving obesity, we have conducted very detailed research. We realized that obesity and child obesity are both huge problems since the rates around the world nowadays are very high. In an attempt to understand the reasons behind this, we designed a questionnaire, so we could test how healthy our classmates’ lifestyle is. Then we contacted a nutritionist and they helped us make an informational leaflet about obesity, which we distributed to others. Lastly, we designed an online game concerning eating habits. While we did our research, we found out that our daily eating choices impact the environment greatly. Thus, changing our eating habits for the better may prove to be the most effective way to help the environment.